Women's work in the field of administration : (Ministry of Higher Education and Scientific Research، for example) - Fawziya Abdulla Mohammed; Fawziya Abdulla Mohammed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
The research is entitled as Women's work in the field of administration (Ministry of Higher Education and Scientific Research, for example) The aim of conducting this research is to Status of women’s work in the administrative fields. And the type of research is descriptive qualitative research. And the methods that were used in it., and methods What was used in this research is the qualitative method, in addition to the social survey method, in order to obtain the method of collecting information, the following methods were relied upon (interview, statistical information). Then the sample was selected intentionally, because from the title of the research. It is clear that the research is about the reality women’s work f, and to determine the size of the sample. It was determined by two ways, the first way, was to identify all the women who have administrative responsibility in the Ministry. And the second way includes the female employee was identified with some of those who had responsibility for the divisions. And at the end of the research. The researcher tried to come up with some results, recommendations and proposal’s purpose of improving the reality of women’s work in the administrative field, with defining their job as employees and managers in the office of the Ministry.